PELAKSANAAN PENYIDIKAN TINDAK PIDANA PENCULIKAN ANAK DI POLSEK PADANG TIMUR TERHADAP LAPORAN POLISI - Nurlinda Yenti, Ikhwanur Aulia dan (Normative Jurnal Ilmiah Hukum, 2022)
The crime of kidnapping children has occurred in today's society. At this time many children are victims due to lack of attention from parents and also environmental conditions that support the occurrence of a crime where the unemployment rate is getting higher and socio-economic problems arise which are marked by increasing crime rates, as well as the development of science and technology that does not always have a positive impact on society. As was the case in 2016 in the jurisdiction of the Padang Timur Police, precisely in front of SDN 03 Bandar Bekali, Padang Timur District, Padang City, where the suspect deliberately took the child away without the permission and knowledge of his parents and then asked for a ransom of Rp. 15,000,000 to the the victim's parents if their child wants to return and the money is planned to be used by the suspect to pay the debt. Criminal acts in the Criminal Code (KUHP) are known as stratbaar feit and in the literature on criminal law the term offense is used. Crime is a term that contains a basic understanding in legal science, as a term formed with awareness in giving certain characteristics to criminal law events.